The Ends of Freedom: Reclaiming America's Lost Promise of Economic Rights - Fligstein, Neil (Journal of Economic Literature, 2023)
Neil Fligstein of Department of Sociology, University of California reviews “The Ends of Freedom: Reclaiming America’s Lost Promise of Economic Rights” by Mark Paul. The Econlit abstract of this book begins: “Explores the role of the state in structuring and limiting the reach of markets, promoting the view that the United States can eradicate poverty and build an economy that works for everyone by adopting social and economic rights.”